2003
DOI: 10.1002/glia.10285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of remyelinating potential of focal and intravenous administration of autologous bone marrow cells into the rat demyelinated spinal cord

Abstract: The remyelinating potential of autologous bone marrow cells was studied after direct injection and following intravenous injection into rats with a demyelinated lesion in the spinal cord. Both focal and intravenous injections of acutely isolated mononuclear bone marrow cell fractions resulted in varying degrees of remyelination. Suspensions of bone marrow cells collected from the same rat were delivered at varied concentrations (10 2 to 10 5 for direct injection and 10 4 to 10 7 for i.v. injections). The lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 37 publications
4
45
0
1
Order By: Relevance
“…Specifically, a number of investigators have reported that adult mouse and human BMSCs can differentiate in vitro into other cell types, including muscle, skin, liver, lung, and neural cells [246][247][248][249][250]. It was also suggested that bone marrow-derived stromal cells can generate astrocytes [251], as wedll as produce myelin and remyelinate a demyelinated lesion of the spinal cord of the rat [252,253]. The potential of stromal cells for cell replacement therapy is still controversial in view of reports showing that stromal cells may rather fuse with existing neurons and glia, resulting in the formation of heterokaryons [248,254].…”
Section: Bone Marrow Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a number of investigators have reported that adult mouse and human BMSCs can differentiate in vitro into other cell types, including muscle, skin, liver, lung, and neural cells [246][247][248][249][250]. It was also suggested that bone marrow-derived stromal cells can generate astrocytes [251], as wedll as produce myelin and remyelinate a demyelinated lesion of the spinal cord of the rat [252,253]. The potential of stromal cells for cell replacement therapy is still controversial in view of reports showing that stromal cells may rather fuse with existing neurons and glia, resulting in the formation of heterokaryons [248,254].…”
Section: Bone Marrow Stromal Cellsmentioning
confidence: 99%
“…Targeting the perivascular niche has been suggested mainly by the intravenous route of cell delivery from which the cells may cross the blood-brain-barrier [253,273,274]. The specific homing of NSCs to the brain was explained in part by the constitutive expression of a wide array of adhesion molecules (integrins, selectins, and so forth) and chemokine receptors by the transplanted cells [273,275].…”
Section: Route Of Cell Deliverymentioning
confidence: 99%
“…In contrast, MSC are thought to improve recovery by tion from bone marrow of patients or other donors. Subsequently, cells can be expanded and used for either auproviding therapeutic factors that render the hostile environment of the adult injured CNS more permissive for tologous transplantation, or stored in "universal donor" (20,32). In the latter studies, authors regene (30) as described previously (33).…”
Section: Introductionmentioning
confidence: 99%
“…Such neural differentiation could be highly relevant for neurological diseases like multiple sclerosis, neurodegenaration and stroke. In animal studies, it was shown by us and others that MSC could induce strong neurotrophic and neuroprotective effects in the murine models of MS (EAE), Parkinson's disease, spinal trauma and ALS (2,(28)(29)(30) . In our previous studies, we have shown that murine and human MSCs can differentiate into neural-like and glial-like cells under specific conditioning by growth factors (2).…”
Section: Discussionmentioning
confidence: 99%